2009
DOI: 10.1518/155534309x441862
|View full text |Cite
|
Sign up to set email alerts
|

Convince Me: Modeling Naturalistic Decision Making

Abstract: This paper is positioned in response to a call for an exchange of dialogue between researchers in the fields of macrocognition and computational modeling. Our work encourages examination of the complementarities that exist between these fields proposing that some of the challenges associated with micromodeling perspectives may be addressed by drawing upon "midgranularity" cognitive architectures. The study documented here demonstrates the value of modeling macrocognitive phenomena using the midgranularity arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Cropp, Banks, and Elghali (2011) compared three models on their ability to capture experts’ decision policies when performing contaminated-land risk assessments, namely, the lens model (i.e., a linear equation typically derived using multiple regression; see Brunswik, 1952), the matching heuristic (a fast-and-frugal heuristic; see Dhami, 2003), and a coherence model (based on the theory of explanatory coherence; see McAndrew, Gore, & Banks, 2009). Results using a cross-validation technique showed that the lens model (i.e., linear regression) provided the best account of experts’ decisions in that task context.…”
Section: Discussionmentioning
confidence: 99%
“…Cropp, Banks, and Elghali (2011) compared three models on their ability to capture experts’ decision policies when performing contaminated-land risk assessments, namely, the lens model (i.e., a linear equation typically derived using multiple regression; see Brunswik, 1952), the matching heuristic (a fast-and-frugal heuristic; see Dhami, 2003), and a coherence model (based on the theory of explanatory coherence; see McAndrew, Gore, & Banks, 2009). Results using a cross-validation technique showed that the lens model (i.e., linear regression) provided the best account of experts’ decisions in that task context.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a coherent account, all the facts are explained or all the contradictory arguments are resolved. Coherence has been proposed as a basis for NDM (Cropp, Banks, & Elghali, ; McAndrew et al ., ) based on the work of Thagard (), but these models do not distinguish between different forms of coherent representation. We suggest that both story building and argumentation‐based decision‐making are based on different forms of representation, but the aim of both is to be coherent.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are some NDM studies in domains that have greater opportunity for analytic decision‐making such as day traders (e.g., McAndrew & Gore, ; McAndrew, Gore, & Banks, ), these studies are less common and there is less understanding of how analytic naturalistic decisions are made. The aim of this study is to develop this understanding by comparing current theoretical explanations of analytic NDM with an alternative account that we propose based on decision‐making through argumentation.…”
Section: Introductionmentioning
confidence: 99%
“…When the model is run, activation spreads throughout the network, and it settles into a state in which the activation of the nodes is stable, given the excitatory and inhibitory links. This theory has been used to model decision making by jurors (Byrne, 1995) and investment fund managers (McAndrew, Gore, & Banks, 2009), providing evidence for the sufficiency of this account of decision making. Defra, 2004).…”
Section: Application Of Decision-making Modelsmentioning
confidence: 99%